Complementary Therapy: Foot and Hand Massage on Reducing Post Laparotomy Pain Levels with Adenomyosis (Case Study) - Alfy Bercy; Ulty Desmarnita (Journal Center of Excellent : Health Assistive Technology, 2023)
Adenomyosis is a disorder of the reproductive system characterized by tissue that lines the uterus growing into the muscular wall of the uterus. At the time after the postoperative patient complained of pain postoperative laparotomy cystectomy. The application of the intervention that will be given to treat pain is the application of foot and hand massage to reduce post-laparotomy pain. The aim of the study was to apply foot and hand massage to reduce post-laparotomy pain levels with adenomyosis. The research method is in the form of evidence based practice. The intervention was carried out for 3 days, with 2 sessions each morning and evening, with pain scale measurements using the NRS and WBFPRS. Intervention is carried out before the administration of medical therapy. Intervention is only done with one sample. The results of the study described a decrease in pain levels after massage. The results obtained by the patient seemed relaxed and able to do activities independently. It can be concluded that foot and hand massage can reduce pain levels in post-laparotomy patients, with a pain scale of NRS 2 and WBFPRS 2.